Isolation and characterization of thermophilic cellulase-producing bacteria from empty fruit bunches-palm oil mill effluent compost - Samsu Baharuddin, Azhari; Abdul Razak, Mohamad Nafis; Lim, Siong Hock; Ahmad, Mohd Najib; Abd. Aziz, Suraini; Abdul Rahman, Nor'aini; Md. Shah, Umi Kalsom; Hassan, Mohd Ali; Kenji, Sakai; Shirai, Yoshihito (Science Publications, 2010)
Problems statement: Lack of information on locally isolated cellulase-producing bacterium in thermophilic compost using a mixture of Empty Fruit Bunch (EFB) and Palm Oil Mill Effluent (POME) as composting materials. Approach: The isolation of microbes from compost heap was conducted at day 7 of composting process where the mixture of composting materials consisted of 45.8% cellulose, 17.1% hemicellulose and 28.3% lignin content. The temperature, pH and moisture content of the composting pile at day 7 treatment were 58.3, 8.1 and 65.5°C, respectively. The morphological analysis of the isolated microbes was conducted using Scanning Electron Microscope (SEM) and Gram stain method. The congo red test was conducted in order to detect 1% CMC agar degradation activities. Total genomic DNAs were extracted from approximately 1.0 g of mixed compost and amplified by using PCR primers. The PCR product was sequent to identify the nearest relatives of 16S rRNA genes. The localization of bacteria chromosomes was determined by Fluorescence In Situ Hybridization (FISH) analysis. Results: Single isolated bacteria species was successfully isolated from Empty Fruit Bunch (EFB)-Palm Oil Mill Effluent (POME) compost at thermophilic stage. Restriction fragment length polymorphism profiles of the DNAs coding for the 16S rRNAs with the phylogenetic analysis showed that the isolated bacteria from EFB-POME thermophilic compost gave the highest homology (99%) with similarity to Geobacillus pallidus. The strain was spore forming bacteria and able to grow at 60°C with pH 7. Conclusion: Thermophilic bacteria strain, Geobacillus pallidus was successfully isolated from Empty Fruit Bunch (EFB) and Palm Oil Mil Effluent (POME) compost and characterized.